Integration of Mathematics with other Sciences - Sunnatullo Do'stov; Suyunova Rano Ruziboy qizi; Khushbokova Saodat Quchor qizi; Zaripova Gulasal Ulugbek qizi (Zien Journals, 2022)
This article is written about the integral relationship of mathematics with other disciplines and the importance of an integrative approach in the effective organization of lessons in this discipline. The interrelationships of mathematics and physics, the educational and methodological significance of integrative approaches were also discussed.
Keywords: integration; problem; classification; differential